HUBUNGAN ANTARA JENIS KELAMIN, USIA DAN BERAT BADAN DENGAN KUALITAS HIDUP TERKAIT KESEHATAN RONGGA MULUT PADA LANSIA DI KOTA DUMAI, PROVINSI RIAU - Intan Batura Endo Mahata; Abu Bakar; Valendriyani Ningrum (Universitas Baiturrahmah, 2022)
Introduction: Changes in the oral cavity due to aging can affect the quality of life-related to oral health. There is limited research related to this in Indonesia, especially in Riau Province, Dumai City. The purpose of this study was to assess the quality of life related to the oral cavity in the elderly and to analyze its relationship to individual characteristics, including gender, age, and weight. Methods: This was a cross-sectional study conducted by the survey of gender, age, weight, and quality of life-related to the oral cavity in the elderly using the Indonesian version of the Geriatric Oral Health Assessment Index (GOHAI) questionnaire consisting of 12 questions. The sampling technique of this study was an accidental sampling method, with a total of 247 respondents. Inclusion criteria are elderly people aged 65 years, not having a history of systemic disease, and not undergoing radiotherapy and chemotherapy. Results: From the results of the study, it was found that respondents with low quality of life were 96.4% (GOHAI score 50), respondents with moderate quality of life were 3.6% (GOHAI score 51-56) and respondents with high quality of life were 0% (GOHAI score 57 -60). The results of the Spearman Rank correlation test between the variables of sex (p-value 0.000), age (p-value 0.002), and body weight (p-value 0.000) on quality of life showed significant results (p <0.05). Conclusion: There is a significant relationship between gender, age, and weight with quality of life-related to the oral cavity in the elderly in Dumai City, Riau Province. Therefore, it is necessary to develop a health policy strategy in an effort to improve the quality of life in the elderly, especially those related to the oral cavity